First reports and generic descriptions of the achlorophyllous holoparasites Apodanthaceae (Cucurbitales) of Colombia (2014)
ABSTRACT: The Apodanthaceae (Cucurbitales) are one of the 12 parasitic clades of flowering plants and the only holoparasitic family with a vegetative phase entirely endophytic, growing primarily on Fabaceae and Salicaceae stems. The two genera of the family, Apodanthes and Pilostyles, are broadly distributed in Colombia, although they remain extremely under-collected and poorly known. Based on feld and herbarium work, and a review of the literature, we provide detailed generic-level descriptions of the family. We also update the records of the family in Colombia and discuss the homology and taxonomic implications of oral characters such as perianth scales, pollen sacs, and the central column. Finally, we provide photographic records of Colombian Apodanthaceae, and some guidelines for properly collecting these plants.